2022
DOI: 10.3390/biom12020232
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanofiber-Based Aerogels from Wheat Straw: Influence of Surface Load and Lignin Content on Their Properties and Dye Removal Capacity

Abstract: Water pollution is one of the most serious problems worldwide. Nanocellulose-based aerogels usually show excellent adsorption capacities due to their high aspect ratio, specific surface area and surface charge, making them ideal for water purification. In this work, (ligno)cellulose nanofibers (LCNFs/CNFs) from wheat straw residues were obtained using two types of pre-treatments: mechanical (Mec) and TEMPO-mediated oxidization (TO), to obtain different consistency (0.2, 0.4, 0.6 and 0.8) bioaerogels, and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 72 publications
1
14
1
Order By: Relevance
“…The highest lignin removal was achieved for CNF1 (98 %), CNF 5.6 (97 %) and CNF3 (96 %).The highest hemicellulose removal was also observed for CNF1 (59 %), followed by CNF 5.6 (50 %) and CNF3 (38 %). This is in line with the common trend of observation due to the decrease of amorphous components like lignin and hemicellulose that easily absorb chemicals, whereas the compactness of the crystalline regions makes it difficult for chemical penetration [22,23]. The cellulose content increased significantly after acid hydrolysis.…”
Section: Compositional Analysissupporting
confidence: 85%
“…The highest lignin removal was achieved for CNF1 (98 %), CNF 5.6 (97 %) and CNF3 (96 %).The highest hemicellulose removal was also observed for CNF1 (59 %), followed by CNF 5.6 (50 %) and CNF3 (38 %). This is in line with the common trend of observation due to the decrease of amorphous components like lignin and hemicellulose that easily absorb chemicals, whereas the compactness of the crystalline regions makes it difficult for chemical penetration [22,23]. The cellulose content increased significantly after acid hydrolysis.…”
Section: Compositional Analysissupporting
confidence: 85%
“…The nanofibrillation yield (η, Table 2 ) for LCMNFs was 48%, while for CMNFs, it was 58%. The lower performance in LCMNFs is associated with the presence of lignin, which causes interference during TEMPO-mediated oxidation, leading to secondary oxidation reactions [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fact that the reinforcing effect is greater with CMNFs than with LCMNFs can again be attributed to the presence of lignin in LCMNFs. It has been recently reported that the presence of lignin interferes with the primary activator (NaClO) during the bleaching process, resulting in aerogels with poorer mechanical properties [ 44 ]. Some authors have reported that a higher aspect ratio of CMNFs results in a higher Young’s modulus of the aerogels when the content of crosslinker employed is less than that of micro/nanofibers [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…. For example, Morcillo-Martín et al removed dyes through aerogels prepared from CNF oxidized by TEMPO, as its surface negative-charged carboxyl groups could remove cationic dyes . Despite these fascinating and unique characteristics, the inefficient network connection and discontinuity of cellulose based aerogels lead to an unsatisfactory mechanical property, low thermal stability, and limited adsorption capacity, which greatly restricts their use in the field of thermal insulation.…”
Section: Introductionmentioning
confidence: 99%